Effect of Uttar Basti on Endometrial Thickness and Ovulation in Women with Thin Endometrium - Lamoria, Sudesh; Arvind Adalinge, Shruti; Meher, Krishna; Meher, Sudeshna (International Research Journal of Ayurveda & Yoga, 2025)
Infertility affects a significant proportion of reproductive-age women globally, and among the various contributing factors, thin endometrium remains a challenging condition to manage. A thin endometrial lining (commonly defined as